ANALYSIS OF THE EFFECT OF DEBT STRUCTURE, FIRM SIZE, SALES GROWTH, AND TOTAL ASSET TURNOVER ON PROFITABILITY IN MANUFACTURING FIRMS LISTED ON THE INDONESIAN STOCK EXCHANGE - Simanjuntak, Gracesiela Yosephine (Asosiasi Dosen Akuntansi Indonesia, 2020)
This research was conducted to test and analyze the influence of debt structure (short-term debt and long-term debt), company size, sales growth and Total turnover of assets to profitability in manufacturing companies Listed on the Indonesia Stock Exchange period 2016-2018. The type of research used by research is Causal Research. The population in this study amounted to 136 manufacturing companies listed on the Indonesia Stock exchange period of 2016 ? 2018 ' with a sample number of 73 companies, selected by a purposive sampling method. Data processing uses multiple linear regression analysis techniques and residual tests with the smallest quadratic equations and hypothesis tests using F ? statistic to test the simultaneous impact and T statistic to test the partial regression coefficient With a significant 5% level. The results of a partial study show that the debt structure (short-term debt) significantly affects profitability. Debt structure (long-term debt has significant negative impact on profitability. Company size and sales growth have significant positive effect on profitability. Total asset turnover has no significant positive impact on profitability. Simultaneously the debt structure (short-term debt and long-term debt), company size, sales growth and Total turnover of assets positively affect profitability.